High‐Entropy Carbonitride MAX Phases and Their Derivative MXenes. Issue 6 (29th December 2021) - Du, Zhiguo; Wu, Cheng; Chen, Yuchuan; Zhu, Qi; Cui, Yanglansen; Wang, Haiyang; Zhang, Yongzheng; Chen, Xiao; Shang, Jiaxiang; Li, Bin; Chen, Weihua; Liu, Chuntai; et al.
Abstract: Although high‐entropy layered transition metal carbonitride MAX phases and their derivative MXenes have been proposed to exhibit unique physicochemical features for widespread applications, it is still challenging to synthesize them owing to the easy formation of separated phases during the traditional synthetic process. Here, a new high‐entropy carbonitride MAX phase (HE CN‐MAX, (Ti1/3 V1/6 Zr1/6 Nb1/6 Ta1/6 )2 AlCx N1–x ) is synthesized on the basis of metallurgically treating medium‐entropy MAX (ME‐MAX) (Zr1/3 Nb1/3 Ta1/3 )2 AlC and other MAX phases (Ti4 AlN3 and V2 AlC). During the metallurgical process, the unique usage of a medium‐entropy MAX phase effectively solves the phase separation issue for the formation of a high‐entropy MAX phase owing to their low entropy difference. After selective extraction of an A species, a high‐entropy carbonitride MXene (HE CN‐MXene) with high mechanical strains and five types of metal‐nitrogen bonds is achieved, which shows good adsorption and catalytic activities for lithium polysulfides. As a result, a lithium–sulfur battery with HE CN‐MXene delivers a high‐rate capability (702 mAh g −1 at 4 C) and good cycling stability. Abstract : A high‐entropy carbonitride MAX phase is synthesized on the basis of metallurgical treatment of a medium‐entropy MAX phase with other MAX phases. After the selective etching of Al species, the derivative high‐entropy carbonitride MXene is achieved, in which there are strong mechanical strains by implanting five types of transition metals, showing high electrocatalytic activities for polysulfides in lithium–sulfur batteries.